Contemporary Traffic Laws from the Perspective of Islamic Law - Knou, Khaled (Journal of Islamic and Religious Studies, 2020)
Modern countries have paid great attention to the issue of traffic safety and considered that transportation is one of the mainstays of the state entity, given the tragic facts left behind by traffic accidents, and they have taken preventive measures to ensure safety on the roads, and to establish special programs to prevent traffic accidents, and to create all conditions of security and traffic safety. For all road users, and these procedures include traffic laws that road users must abide by and abide by, and in case of violation, there are penal penalties; To deter individuals and society. It is known that these laws are among the contemporary issues and issues that the early scholars of the nation did not talk about, so it was necessary to examine this issue from a jurisprudential perspective; To show the world the realism of Islam, and the comprehensiveness of its rulings that regulate all aspects of life. Therefore, this research came in response to this problem, which is represented in the jurisprudential rooting of the contemporary rules and laws that regulate traffic in terms of its organization, and in terms of finding deterrent penalties for those who violate it.